Removing Harmful Options: The Law and Ethics of International Commercial Surrogacy. (23rd December 2019) - Hodson, Nathan; Townley, Lynne; Earp, Brian D
Abstract: Focusing on the UK as a case study, this article argues that having the choice to enter into an international commercial surrogacy arrangement can be harmful, but that neither legalisation nor punitive restriction offers an adequate way to reduce this risk. Whether or not having certain options can harm individuals is central to current debates about the sale of organs. We assess and apply the arguments from that debate to international commercial surrogacy, showing that simply having the option to enter into a commercial surrogacy arrangement can harm potential vendors individually and collectively, particularly given its sexed dimension. We reject the argument that legalizing commercial surrogacy in the UK could reduce international exploitation. We also find that a punitive approach towards intended parents utilizing commercial rather than altruistic services is inappropriate. Drawing on challenges in the regulation of forced marriage and female genital cutting, we propose that international collaboration towards control of commercial surrogacy is a better strategy for preserving the delicate balancing of surrogate mothers' protection and children's welfare in UK law.